2008
DOI: 10.1080/08995600802345220
|View full text |Cite
|
Sign up to set email alerts
|

Technology as a Tool for Leadership Development: Effectiveness of Automated Web-Based Systems in Facilitating Tacit Knowledge Acquisition

Abstract: The effectiveness of emerging technology in helping to develop the tacit or experience-based knowledge needed for effective leadership performance was demonstrated in an on-line environment for discussion and training. One hundred and twenty-seven military students participated in three 20-minute discussions in one of three learning environments: standard classroom; standard on-line discussion; and discussion assisted by semantic technology. Consistent with expectations, semantic technology-supported learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…For example, a number of studies reported positive correlations between mastery-approach goals and transfer of training (e.g. Boyce et al, 2008;Chiaburu et al, 2010;Dragoni et al, 2009;Laine & Gegenfurtner, 2013;Nordstrom et al, 1998;Tziner et al, 2007;Van de Walle et al, 2010;Wilson et al, 2002). A few studies also identified negative correlations between masteryapproach goal orientation and transfer (Holladay & Quiñones, 2003), particularly in training programs that were mandated (Orvis et al, 2009;Towler & Dipboye, 2001).…”
Section: Goal Orientations and Transfer Of Trainingmentioning
confidence: 99%
“…For example, a number of studies reported positive correlations between mastery-approach goals and transfer of training (e.g. Boyce et al, 2008;Chiaburu et al, 2010;Dragoni et al, 2009;Laine & Gegenfurtner, 2013;Nordstrom et al, 1998;Tziner et al, 2007;Van de Walle et al, 2010;Wilson et al, 2002). A few studies also identified negative correlations between masteryapproach goal orientation and transfer (Holladay & Quiñones, 2003), particularly in training programs that were mandated (Orvis et al, 2009;Towler & Dipboye, 2001).…”
Section: Goal Orientations and Transfer Of Trainingmentioning
confidence: 99%
“…9 A few projects articles have described individual military personal technologies. [10][11][12] Most studies of health-related personal technologies have been confined to the civilian arena. [13][14][15][16][17] With the rapidly growing sophistication of personal technology, knowledge must be continuously updated to be useful.…”
Section: Introductionmentioning
confidence: 99%
“…A tailored intervention would identify the most needed skills and present the corresponding activities that the learner should work on. This approach of training, combined with the sharing of tacit knowledge (Le Bellu, Lahlou, & Nosulenko, 2010), has shown success in various fields, such as leadership development (Boyce, LaVoie, Streeter, Lochbaum, & Psotka, 2008;Hedlund et al, 2003), and has yet to be tried in improving teen drivers' hazard perception skills.…”
Section: Discussionmentioning
confidence: 99%